Two-boxing is irrational - Noonan, Harold (Springer, 2015)
Philosophers debate whether one-boxing or two-boxing is the rational act in a Newcomb situation. I shall argue that one-boxing is the only rational choice. This is so because there is no intelligible aim by reference to which you can justify the choice of two-boxing over one-boxing once you have come to think that you will two-box (whereas there is such an aim by reference to which you can justify one-boxing). The only aim by which the agent in the Newcomb situation can justify his two-boxing is the subjunctively described aim of ‘getting more than I would if I were to one-box’. But such a subjunctively described aim can justify an action only if it can be seen as generating, in conjunction with the agent’s beliefs, an indicatively describable aim which justifies the action. In the case of the Newcomb agent the aim of 'getting more than I would if I were to one-box’ cannot be seen in this way.